Sistem Pendukung Keputusan Pemilihan Program Studi Mahasiswa Baru Menggunakan Metode SAW Di Universitas Ibrahimy - Siti Maulidatul Hasanah; Farihin Lazim; Firman Santoso (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
The selection of a study program is a strategic step for prospective new students, as itinfluences long-term academic success and career outcomes. However, many prospectivestudents find it difficult to choose a study program that aligns with their interests andabilities, which can reduce their motivation to learn and increase the likelihood of droppingout. This study aims to develop a web-based decision support system capable of providingobjective study program recommendations using the Simple Additive Weighting (SAW)approach at Ibrahimy University Sukorejo Situbondo. The SAW method was chosenbecause it is simple, efficient, and capable of ranking alternatives based on predeterminedcriteria weights. The criteria used include Academic Potential Test (TPA) with a weight of20%, General Knowledge Test (TPU) 20%, Arabic Language 10%, English Language10%, Study Program Competency Test 30%, and Psychology Test 10%. The systemdevelopment follows the waterfall model, including the stages of requirements analysis, system design, implementation using PHP and MySQL, testing, and maintenance. Theresults show that the developed system is able to perform matrix normalization, calculatethe preference score (Vi) for each study program alternative, and generate accurate andefficient recommendation rankings. This system makes it easier for prospective newstudents to choose a study program that matches their potential, while also assistingIbrahimy University in carrying out a more structured, transparent, and measurableselection process.